METABOLIC FATE OF RADIOACTIVE DIGITOXIN IN HUMAN SUBJECTS - Okita, George T.; Talso, Peter J.; Curry, John H.; Smith, Frederick D.; Geiling, E.M.K. (The Journal of pharmacology and experimental therapeutics, 1955)
Biosynthetically labeled C14-digitoxin was administered intravenously in multiple doses to three terminal patients. The various tissue samples obtained at autopsy were assayed for both the unchanged drug and its metabolic products. The myocardium does not have any special affinity for the cardiac glycoside in comparison to other organs. On a tissue-weight basis the kidney and the contents of the gall bladder, jejunum, ileum, and colon have the highest concentration of unchanged digitoxin. The gall bladder contents, jejunum contents, and spleen have the highest concentration of metabolic products. On a whole organ basis the liver has the largest amount of both digitoxin and its metabolic products. The majority of the administered glycoside is metabolized in the body with the liver being the major organ involved in the detoxification of the drug. The kidney is the major organ involved in the ultimate removal of digitoxin and its metabolic products. The probable pathway for the metabolic fate and excretion of C14-digitoxin in terminal patients has been discussed.